Between philology and theology : contributions to the study of ancient Jewish interpretation - García Martínez, Florentino. (Supplements to the Journal for the Study of Judaism, 2013)
The essays by Florentino García Martínez collected in this volume reflect some of his most recent work on theological concepts as they are formed in the interpretations and in the imagination of ancient Jewish writers, and thus illuminate the nexus between philology and theology. The essays, five of which are published for the first time in English, engage a broad range of ancient Jewish texts ranging from Philo and the Dead Sea Scrolls, to Jubilees, 4 Ezra and the Targumim. Focus of the essays is the way in which ancient Jewish writers (and, in the case of 4 Ezra, Christian Renaissance authors) are interpreting and transforming earlier biblical traditions and how these new interpretations shape theological concepts.